PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SDN 004 TERATAK BULUH KECAMATAN SIAK HULU KABUPATEN KAMPAR - Desima Silalahi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The role-playing method is a method of role-playing by providing real experience in learning. The research method used was classroom action research, this study was conducted in two cycles and each cycle was conducted three times. Data collection techniques in this study used teacher observation sheets, student activity sheets, and student learning outcomes. Learning tools consist of the syllabus, and plan for implementing learning. Learning outcomes in the first cycle, the number of students who get a high classification score amounted to 9 people with a percentage of 36%, and a moderate classification of 16 people with a percentage of 64%. In the second cycle, the results of high classification learning were 20 people with a percentage of 80%, and in the middle classification, there were 5 people with a percentage of 20%. So it was concluded that using the role-playing method can improve learning outcomes of PKn.